JURIDICAL ANALYSIS OF TAX CRIME (Case Study Judgment No : 268/Pid.B/2020/PN.SBY) - Asep Rosyidin Kanny; Vera Rimbawani Sushanty (Universitas Islam Lamongan, 2022)
Abstract Taxes are the main source of national revenue, with a portion of approximately 83% of the total sources of national revenue for the Republic of Indonesia. No one is really willing to pay taxes, especially because the taxpayers receive no direct counter compensation for spending their money to pay the tax. So it is necessary to enforce the criminal tax law so that taxpayers are obedient in fulfilling their tax obligations. Tax crime are regulated in the Act on General Provisions and Tax Procedures.